2022
DOI: 10.3390/cancers14143547
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinases in Cancers: Aspects of Proliferation, Metastasis, and Apoptosis

Abstract: Deubiquitinases (DUBs) deconjugate ubiquitin (UBQ) from ubiquitylated substrates to regulate its activity and stability. They are involved in several cellular functions. In addition to the general biological regulation of normal cells, studies have demonstrated their critical roles in various cancers. In this review, we evaluated and grouped the biological roles of DUBs, including proliferation, metastasis, and apoptosis, in the most common cancers in the world (liver, breast, prostate, colorectal, pancreatic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 192 publications
0
9
0
Order By: Relevance
“…It is testified that USP37 could directly deubiquitinate c‐Myc in a deubiquitinase‐dependent manner to promote lung cancer cell proliferation and induce aerobic glycolysis (the Warburg effect). 13 , 16 As a multifunctional proto‐oncogene, c‐Myc can regulate cell division, growth, autophagy, and apoptosis. 17 , 18 , 19 In this study, we testify that USP37 could promote fibroblasts proliferation and collagen production in keloid with up‐regulated c‐Myc accumulation or expression, which indicates the ubiquitin‐specific peptidase function of USP37 to post‐translational regulate the expression of c‐Myc.…”
Section: Discussionmentioning
confidence: 99%
“…It is testified that USP37 could directly deubiquitinate c‐Myc in a deubiquitinase‐dependent manner to promote lung cancer cell proliferation and induce aerobic glycolysis (the Warburg effect). 13 , 16 As a multifunctional proto‐oncogene, c‐Myc can regulate cell division, growth, autophagy, and apoptosis. 17 , 18 , 19 In this study, we testify that USP37 could promote fibroblasts proliferation and collagen production in keloid with up‐regulated c‐Myc accumulation or expression, which indicates the ubiquitin‐specific peptidase function of USP37 to post‐translational regulate the expression of c‐Myc.…”
Section: Discussionmentioning
confidence: 99%
“…It can be reversed by deubiquitinating enzymes (DUBs), a group of over 100 enzymes divided into five families: ubiquitin-specific proteases (USPs); ovarian tumor proteases (OTUs); ubiquitin C-terminal hydrolases (UCHs); Machado–Joseph disease protein domain proteases (MJDs); and JAMM motif proteases [ 5 ]. Particular DUBs catalyze the removal of ubiquitin particles from different ubiquitinated proteins, which leads to the regulation of the stability and activity of the target particles [ 5 , 6 ]. This process is crucial for controlling various cellular pathways, such as DNA repair, gene expression, protein localization, kinase activation, cell cycle progression, or cell apoptosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particular DUBs catalyze the removal of ubiquitin particles from different ubiquitinated proteins, which leads to the regulation of the stability and activity of the target particles [ 5 , 6 ]. This process is crucial for controlling various cellular pathways, such as DNA repair, gene expression, protein localization, kinase activation, cell cycle progression, or cell apoptosis [ 6 ]. The growing body of evidence suggests that dysregulation of the DUBs system can contribute to the development of a variety of cancers, including BC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, two E1s, 38 E2s, and approximately 600–1000 E3s have been found so far ( 22 ). Studies have found that ubiquitination and deubiquitination reactions are responsible for developing various tumors and play key roles in cancer treatment ( 23 ). The ubiquitinization and deubiquitination process is shown in the Figure 1 .…”
Section: Introductionmentioning
confidence: 99%